Facing Ethical Challenges in the Workplace: Conceptualizing and Measuring Professional Moral Courage - Sekerka, Leslie E.; Bagozzi, Richard P.; Charnigo, Richard (Journal of business ethics, 2009)
Scholars have shown renewed interest in the construct of courage. Recent studies have explored its theoretical underpinnings and measurement. Yet courage is generally discussed in its broad form to include physical, psychological, and moral features. To understand a more practical form of moral courage, research is needed to uncover how ethical challenges are effectively managed in organizational settings. We argue that professional moral courage (PMC) is a managerial competency. To describe it and derive items for scale development, we studied managers in the U.S. military and examined prior work on moral courage. Two methods were used to measure PMC producing a five dimensional scale that organized under a single second-order factor, which we termed overall PMC. The five dimensions are moral agency, multiple values, endurance of threats, going beyond compliance, and moral goals. Convergent and discriminant validity are analyzed by use of confirmatory factor analysis procedures. We conclude by presenting a framework for proactive organizational ethics, which reflects how to support PMC as a management practice.